A blow-up result for a nonlinear wave equation with variable-exponent nonlinearities. Issue 9 (4th July 2017) - Messaoudi, Salim A.; Talahmeh, Ala A.
Abstract: In this paper, we consider the following wave equation: in which is a nonnegative constant and the exponents of nonlinearity are given functions. For arbitrary positive initial energy, we prove a finite-time blow-up result.